Development of an Augmented Reality-Based Interactive Digital Module for Biology Learning at High School 76 Jakarta - Arifin, Muhammad; Rahmatullah, Zaid Hidayat (Journal of Science and Mathematics Education, 2025)
This research aims to develop an interactive digital module based on Augmented Reality (AR) for biology learning at High School 76 Jakarta, focusing on enhancing students’ conceptual understanding and engagement. The development process adopted the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The module was designed to complement the biology curriculum for Grade 11, particularly in the topic of human organ systems. AR technology was integrated to provide three-dimensional visualizations of biological structures, allowing students to interact directly with virtual models through smartphones or tablets. Validation was carried out by media experts, content experts, and biology teachers, showing high feasibility scores across functionality, accuracy, and instructional design criteria. The implementation involved 35 students in a limited field trial, and results from questionnaires and learning outcomes indicated a significant increase in student motivation and conceptual mastery. Moreover, students reported that the AR features facilitated deeper understanding and made abstract biological concepts more tangible. This research concludes that AR-based digital modules are effective tools to support innovative and engaging biology learning. Future studies are suggested to expand implementation at different educational levels and explore long-term learning impacts. The integration of AR in biology education offers promising potential in transforming traditional classrooms into immersive, technology-enhanced learning environments.